The teacher who decides to investigate his own practice - Machuca Rangel, Vikter Rosa (Rastros Rostros, 2002)
It is the wish of today’s educators to qualify their pedagogical competence, for which they should question their teaching profile, whether they are transmitters of knowledge or whether they are reflective professionals who inquire about their own practice.